2021
DOI: 10.1259/dmfr.20200295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different teaching methods in the radiographic diagnosis of proximal carious lesions

Abstract: Objectives: To evaluate four different teaching methodologies in the radiographic diagnosis of proximal carious lesions and in the students’ perception of these methodologies. Methods: 71 undergraduate dental students were subdivided into four groups according to the teaching methodologies used [traditional, hybrid, e-learning and problem-based learning (PBL)]. All methods were applied by two properly trained researchers. Initially, students completed a pre-methodology test (index test). After applying the tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
5
1
6
Order By: Relevance
“…This result is partially in line with our finding of consistently high performance in both pre‐pandemic (blended learning) and pandemic (online‐only) groups. Contrary to Rocha et al, 20 however, our results suggest a positive effect of additional VBLMs in online‐only blended learning.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This result is partially in line with our finding of consistently high performance in both pre‐pandemic (blended learning) and pandemic (online‐only) groups. Contrary to Rocha et al, 20 however, our results suggest a positive effect of additional VBLMs in online‐only blended learning.…”
Section: Discussioncontrasting
confidence: 99%
“…The subject of oral radiology may be particularly suitable for implementation in online‐only concepts since it includes a variety of digital images that can be conveniently accessed and viewed online 18,19 . Interestingly, the only previous study the authors are aware of that compared blended and online‐only learning (and also F2F and problem‐based learning) in oral radiology did not find any significant differences in students' performance between these learning concepts 20 …”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…It could be speculated that many undergraduate dental students who used the DLT were encouraged by their professors to use it as an extra-class activity, and therefore, their professors may have asked them to submit the final certificate as confirmation of accomplishment. [18] compared different teaching methodologies for the training of radiographic detection of proximal carious lesions. The authors observed that students preferred active or a hybrid (blended) methodology, reporting to be easy to learn, making themselves feel more confident in performing the trained diagnosis.…”
Section: Discussionmentioning
confidence: 99%